Volume 7: Turbomachinery, Parts A, B, and C 2011
DOI: 10.1115/gt2011-45425
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Design and Optimization of a Transonic Rotor in Axial Flow Compressors

Abstract: This paper presents a 3-D optimization of a moderately loaded transonic compressor rotor by means of a multi-objective optimization system. The latter makes use of a Differential Evolutionary Algorithm in combination with an Artificial Neural Network and a 3D Navier-Stokes solver. Operating it on a cluster of 30 processors enabled the optimization of a large design space composed of the tip camber line and spanwise distribution of sweep and chord length. Objectives were an increase of efficiency at unchanged s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Hence, on top of the complexity of controlling a high-speed flow with adverse pressure gradients, the airfoil design must handle complex shock-boundary layer interactions in conjunction with aggressive profile cambering, while trying to avoid local stall. A compressor rotor blade shape optimization, aimed at reducing losses by minimizing the shock-boundary layer interaction, is described by Okui et al [95], who used a multi-objective optimization method. The optimization, based on the response from RANS, produced complex three-dimensional shapes along the lines described by Taylor and Miller [138] and McNulty et al [77].…”
Section: High-pressure Compressormentioning
confidence: 99%
“…Hence, on top of the complexity of controlling a high-speed flow with adverse pressure gradients, the airfoil design must handle complex shock-boundary layer interactions in conjunction with aggressive profile cambering, while trying to avoid local stall. A compressor rotor blade shape optimization, aimed at reducing losses by minimizing the shock-boundary layer interaction, is described by Okui et al [95], who used a multi-objective optimization method. The optimization, based on the response from RANS, produced complex three-dimensional shapes along the lines described by Taylor and Miller [138] and McNulty et al [77].…”
Section: High-pressure Compressormentioning
confidence: 99%
“…Its influences on performance are results of trade-off among all the influencing factors", ensure the need for consideration of other critical design parameters for a better aerodynamic design, such as tailored blading (or blade camber line and thickness distributions), solidity and aspect ratio, etc. Okui et al [8] demonstrated a 3D optimization of a large design space by changing sweep, tip camber lines and spanwise chord lengths in transonic rotor design. Interestingly they claimed that the highest efficiency gain was obtained with backward sweep and an optimized S-shaped camber line without losing a stall margin.…”
Section: Numerical Efforts Of Aerodynamic Re-design In a Single-stagementioning
confidence: 99%
“…Another example is performed to show different geometries that prove the 3DBGB capabilities. A compressor blade section is created which is similar to 90% height section of transonic axial compressor rotor created by Okui et al [24] shown in figure 36. Figure 35 shows the chord wise camber line distribution of S-shape compressor blade that Okui et al [24] created.…”
Section: Mach Number Distributionmentioning
confidence: 99%
“…This demonstrates the flexibility of defining the second derivative to create the camber line . Figure 35: The chord-wise distribution of S-shape (90%Height) section [24]. Another supersonic fan section is created to match the ARL supersonic compressor cascade [25].…”
Section: Mach Number Distributionmentioning
confidence: 99%